Hungarian Monitoring, 25 October 1988 . [Magyar rádiófigyelő], 1988. október 25 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Former opponents meet in person; television link between Cologne and Stalingrad - Was Olof Palme murdered by Kurds? - Clouds gather above Polish national roundtable - West German-Soviet summit ends in agreement Domestic Affairs: - Károly Grósz in Iran - Hungarian and Chinese experiences of reform: Political committee member János Lukács continues exchange of view in China - "Conflicts cannot be solved by either military or ideological means" says Bishop Károly Tóth, Hungarian representative at the Christian Conference in Prague - Professor Imre Nagy during his American study tour: "Gabčíkovo-Nagymaros hydroelectric power station could be operated in an environmentally friendly way by pursuing dynamic energy demands" - Unemployment benefit to be introduced in Hungary from 1st January - Romanian national minorities Economy: - "Our aim is for the entrepreneurial spirit to dominate in the Hungarian economy": Károly Grósz announces to American travel experts Külpolitika: - Egykori ellenségek egymással szemközt; Köln-Sztálingrád TV-híd - Kurdok ölték meg Palme miniszterelnököt? - Gyülekeznek a felhők a lengyel nemzeti kerekasztal fölött - Egyetértésben zajlik a nyugatnémet-szovjet csúcs Belpolitika: - Grósz Károly Iránban - A magyar és kínai reform tapasztalatairól Kínában folytat eszmecserét Lukács János PB tag - "A konfliktusokat sem katonai, sem ideológiai eszközzel nem lehet megoldani" - Véli Tóth Károly püspök, aki a Keresztyén Konferencia magyar résztvevője Prágában - Dinamikus energiaigény követésével lehetséges környezetbarát módon üzemeltetni a bős-nagymarosi vízerőművet, - Állítja amerikai tanulmányútja után dr. Nagy Imre professzor - Január elsejétől bevezetik a munkanélküli segélyt Magyarországon - Romániai nemzetiségek ügye Gazdaság: - "Célunk, hogy a magyar gazdaságban a vállalkozói szellem váljék uralkodóvá" - Jelentette ki Grósz Károly az amerikai utazási szakemberek előtt